Potential For Using Native Species From Rocky Fields In An Ecological Landscape - Fraga Xavier, Nara Vanessa; Almeida, Elka Fabiana Aparecida; Fonseca , Rubia Santos; Nunes, Claudineia Ferreira; Isaias , Rosy Mary dos Santos (Revista Unimontes Científica, 2024)
Objective: Focusing on native species of the rocky fields of Serra de Itacambira, Minas Gerais state, Brazil, we analyzed physiological and structural traits of leaves, flowers or of the plant as a whole toward selecting out species with potential use for ecological landscaping. Methodology: A total of 61 plant species belonging to 29 families were collected, analyzed, and the characteristics of their flowers, leaves, and stems were described. Results: These species were pointed out for uses in landscaping, as vertical gardens, roofing of buildings, borders, mass flower designs, and even isolated use in beds. Twenty three out of the 61 identified species were highlighted for supporting low water availability and having a high interaction with local fauna.Conclusion: Based on their structure and physiological traits, the 61 plant species collected in Serra da Itacambira have potential use in ecological landscaping, especially in drought-resistant gardens.